Investigations on the treatment of the subclinical mastitis by penicillin - streptomycin in dry cows - Tevfik TEKELİ; Tülay BAYSAL; Yılmaz GÖKÇAY (Eurasian Journal of Veterinary Sciences)
In this study, the effects of penicilin - streptomycin on subclinical mastitisin dairy cattle was investigated during the dry period. The milk samples of 39 cows that were at the end of the lactation period were collected aseptically. They were examined bact;riologically whether they were infected or not. Pathogenic bacteriae were isolated from 46 milk samples. Then, 46 infected quarters were treated by penicillin- streptomycin combatination. To determine the effectiveness of the treatment, milk samples were collected from the mammary quarters after calving and were examined bacteriologically. After calving 84.78% of these infected quarters were found to be free from infection. Streptococci and E. Coli were eliminated by 100% and staphylococci and C. bovis infections were eliminated 85% during the same period.